2014
DOI: 10.1177/001979391406700208
|View full text |Cite
|
Sign up to set email alerts
|

Economic Development and Sectoral Unions in China

Abstract: Drawing on qualitative fieldwork in China's Guangdong and Zhejiang Provinces, the author asks how post-socialist unions respond to worker unrest and why the development of sectoral-level bargaining has been uneven in different regions of China. While Zhejiang has had relative success in establishing the organizational infrastructure for sectoral bargaining, Guangdong has had little success despite ongoing attempts by unions. The author explains variation in sectoral-level bargaining through an analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 49 publications
0
30
0
3
Order By: Relevance
“…Although decentralization has been the unmistakable trend over the past 30 years, recently there have been some countervailing tendencies towards modest centralization. This has been particularly apparent in the sanitation industry in Guangzhou, which after being radically marketized and decentralized after WTO entry in 2001 experienced ongoing strike waves (Friedman, 2014a). Another highly publicized effort in Wuhan led to city-wide bargaining in the food and beverage industry, and the final agreement claimed to cover 450,000 employees.…”
Section: Collective Bargaining Experimentsmentioning
confidence: 99%
“…Although decentralization has been the unmistakable trend over the past 30 years, recently there have been some countervailing tendencies towards modest centralization. This has been particularly apparent in the sanitation industry in Guangzhou, which after being radically marketized and decentralized after WTO entry in 2001 experienced ongoing strike waves (Friedman, 2014a). Another highly publicized effort in Wuhan led to city-wide bargaining in the food and beverage industry, and the final agreement claimed to cover 450,000 employees.…”
Section: Collective Bargaining Experimentsmentioning
confidence: 99%
“…Similar to that of decentralized and formalistic bargaining, the reasons for ineffectiveness at this level include the union's focus on formalistic terms, the absence of strict enforcement, and often, worker ignorance of the terms of the agreement, or that they were represented by a union (a frequent issue when union representatives are not directly elected) (Wu, 2012). A classic example here is Friedman's (2014b) study of sectoral bargaining in Rui'an eyeglass cluster in Zhejiang Province, where workers interviewed indeed knew nothing about the industry level contract that covered them. Probably the best-known case of failure of enforcement of collective bargaining can be found in Wuhan, where the local government, in a top-down process initiated sectoral negotiations in 2011 in the restaurant industry.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these issues, the ACFTU continues to focus on building collective bargaining institutions at the industry and regional levels. In Guangzhou, for instance, the official union has organized the construction industry, although no collective bargaining has been successfully achieved (Friedman, 2014b). In addition, union organizing by region has also been identified in areas with clusters of small businesses, such as community unions, village union associations, market unions, office building unions, and union associations by ownership in development zones (Liu, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto, Chinese labor union scholars were mainly interested in whether labor unions could protect employees' rights and whether they were independent from the Chinese central government (Zhang, 2009;Lu, Tao & Wang, 2009;Friedman, 2014). In a recent review by Zhang (2009), he concluded that: (1) Chinese unions were not completely independent from the government, but their role was changing, and the government gave unions supports in the protection of workers' rights; (2) There were different types of unions, serving different purposes, and some of them had conflicting interests (e.g., government organized unions versus enterprise organized unions).…”
Section: Introductionmentioning
confidence: 99%